Estudo da produção de biofilme de isolados de Leptospira spp - Gomes, Dayane Olímpia (2016)
Leptospirosis is a zoonotic disease caused by a bacterium that can live a long time in appropriate environmental conditions. Biofilms are aggregations of microorganisms, has a defined architecture, and provides an ideal environment for the exchange of genetic material between cells, beyond to providing protection, temperature resistance and antimicrobial. As it happens with other spirochetes, the leptospira can change their morphology according to environmental changes, and these changes include the formation of biofilms. However are few research with biofilms produced by Leptospira spp, especially on isolated from clinical frames. The aim of this study was evaluate biofilm formation by four clinical isolates of Leptospira interrogans serovar Icterohaemorrhagiae e Canicola. For evaluation of biofilms in vitro and antimicrobial susceptibility, the following tests were performed: adhesion test on polystyrene plate, quantification of protein and polysaccharide, test for minimum inhibitory concentration with three antimicrobials drugs and three different doses. For visualization of the formed biofilm was performed confocal laser microscopy. In the adhesion test on polystyrene plate, all isolates were strongly adhered, characterized as having more polysaccharide than protein. In this research, tests shown that the isolated pathogenic of Leptospira spp has formed biofilm, and they possess antimicrobial resistance to high doses of antibiotics that are used routinely in animal and human clinical.